Higher frequency of the ACTN3 R allele + ACE DD genotype in japanese elite wrestlers - Kikuchi, N.; Min, S.-K.; Ueda, D.; Shoji, N.; Nakazato, K. (The Journal of Strength and Conditioning Research, 2012)
In this study, the authors investigated the association between the ACTN3 and angiotensin-converting enzyme (ACE) genotypes and the performance of 135 Japanese elite male wrestlers. Fifty-two wrestlers had participated in world championships, including the Olympic Games, or had placed first in Japanese national championships and were classified as "international." The remaining 83 wrestlers were classified as "national." The control group consisted of 333 healthy Japanese college students majoring in physical education. In the ACTN3 genotype distribution, a significant difference between the international and control groups was observed (p < 0.05). The ACE genotype distribution and allele frequency of all wrestlers significantly differed from those of the control subjects (p < 0.001). As compared with the control group, the odds ratio of the ACTN3 R allele + ACE DD genotype being international or national was 3.85 (95% confidence interval [CI], 2.10-7.03) or 1.37 (95% CI, 0.79-2.36), respectively. Our data suggest that the combination of ACTN3 and ACE gene polymorphisms is associated with the athletic status of Japanese elite wrestlers.